Effect of Extrusion Process on Mechanical, Welding, and Corrosion Behaviour of 6XXX Series of Aluminium Alloys - Guner, Mehmet Bugra; Konar, Murat; Ozcelik, Gorkem; Demirkiran, Tolga; Hazar, Afife Binnaz Yoruc (SPRINGER INTERNATIONAL PUBLISHING AG, 2021)
Extrusion is a solid-state metal forming process that utilizes heat and excessive deformation to shape materials with constant cross sections. In this forming mechanism, microstructure evolves to variants of fibrous and equiaxed grains with the effects of deformation and recrystallization mechanisms. Besides mechanical properties, welding capabilities and corrosion resistance of 6XXX series of aluminum alloys also affected from extrusion process. In this study, changes on microstructure and mechanical properties that triggered from extrusion process parameters were investigated to gain knowledge about welding and corrosion behavior for 6XXX series aluminum alloys.
Keywords: Aluminium; Extrusion; Microstructure; Corrosion; Welding; Electrochemistry; Materials Science; Metallurgy & Metallurgical Engineering